PENGARUH INTEGRITAS, OBYEKTIVITAS, KERAHASIAAN, KOMPETENSI, INDEPENDENSI, KEPUASAN KERJA DAN ETIKA PROFESI TERHADAP KINERJA AUDITOR (Studi Empiris Pada Inspektorat Provinsi Jawa Tengah) - Cynthia Pitasari, 14.05.52.0239; Badjuri, Achmad (Students Journal of Accounting and Banking, 2017)
The purpose of this research to analyze the influence of integrity, objectivity, confidentiality, competence, independence, job satisfaction and professional ethics to the performance of auditors at the Inspectorate of Local Government in Central Java.Â The population in this research is auditor and all apparatus of Inspectorate of Central Java Provincial Government involved in examination task with having experience working minimum 2 years, Sampling was conducted using a purposive sampling method and number of samples of 55 respondents. The data were obtained from the primary source,collected by using survey method by distributing questionnaire directly.The data analysis technique used in this research is the technique of multiple regression analysis The results showed that the integrity, objectivity, confidentiality, competence, independence, job satisfaction and professional ethics had a significant positive effect on auditor performance.Keywords: Integrity, Objectivity, Confidentiality, Competence, Independence, Job Satisfaction, Professional Ethics And Auditor PerformanceÂ